Three new species of earthworms belonging to the genus Amynthas (Oligochaeta: Megascolecidae) from Hainan Island, China - Sun, Jing; Zhao, Qi; Qiu, Jiang-Ping (Zootaxa, 2010)
This paper describes three new species of earthworms from Hainan Island, China: Amynthas trapezoides sp. nov., Amynthas conchipapillatus sp. nov. and Amynthas dongfangensis sp. nov. Amynthas trapezoides has no pigment, and has two pairs of spermathecal pores in 6/7 and 7/8 arranged trapezoidally near the mid-ventral line, a complicated glandular region on ventral side of 1/2XVII–1/4XIX, developed prostates and repeatedly curved prostatic ducts close to ventral midline. Amynthas conchipapillatus sp. nov. has no pigment, and has a pair of large convex smooth shellfish-like papillae in male pore region, only one pair of spermathecal pores in 5/6 and undeveloped thin prostates which closely adherent to the body wall. Amynthas dongfangensis sp. nov. has a pair of male pores on the centre of a flat-topped conical protuberance surrounded by three to five circular folds, and five pairs of spermathecal pores in 4/5–8/9.